PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MAHASISWA FAKULTAS HUKUM UNIVERSITAS SABURAI - Dendi Firnando (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This study aims to determine the effect of learning motivation on the learning outcomes of Saburai University Law Faculty students. This research uses a quantitative research approach with a descriptive approach. Descriptive approach is the most basic form of research. Intended to describe the phenomena that exist, both natural phenomena or human engineering. This research was conducted at the University of the Earth Ruwa Jurai (SABURAI) in 2020. The data collection method in this study used a questionnaire (questionnaire) method. Data from 32 Saburai University Law Faculty students. This study uses a sampling technique used in this study is nonprobability sampling with purposive sampling method. The results showed that there was an influence of positive and significant learning motivation on the learning outcomes of Saburai University Law Faculty students.